STUDI ANALISIS PEMBENTUKAN UNDANG- UNDANG NOMOR 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH DALAM PERSPEKTIF POLITIK HUKUM NASIONAL - Adibah, Ayuk Wahdanfiari (An-Nisbah: Jurnal Ekonomi Syariah, 2016)
The background of this research is based on an assessment of Islamic law are more likely to provide input for the establishment of national law because it must be recognized that the majority of Indonesia’s population is Muslim andbesides it is also good relation between the State and Muslims have implicationswhich are positive for the development of Islamic legal legislation became anational positive law. Then, how does the history of the formation of law number 21 of 2008 concerning Islamic banking? How national legal political conditions during the formation of the law number 21 of 2008 concerning Islamic banking? And the last, how is the analysis of the formation of law number 21 of 2008 concerning Islamic banking in the political perspective ofnational law? Genealogically, the authors concluded that the promulgation of Law No. 21 of 2008 concerning Islamic Banking is not free of configuration  sand tight political struggles, the determination of these laws have a strong foundation juridical, sociological or philosophical that can later be accounted for. Positivasi about Islamic Banking proves that Islamic law has become asource of national law and have the opportunity to contribute the maximumin the development of national law in the future.Keywords: Islamic banking, Law number 21 of 2008, Political of law